Aplikasi Edible Coating Berbasis Limbah Tulang Ikan Patin Pada Produk Smoked Catfish Kabayaki - Lasmi, Leni; Putra, Yudha Perdana; Nainggolan, Kristina Novalina (Jurnal Kelautan, Lingkungan, dan Perikanan, 2024)
The patin catfish process into smoked catfish kabayaki will produce organic wastes such as fishbones. One of the fish waste handling method is to process the waste into derivative product such as gelatin which can be utilized further as an edible coating precursor. The aim of the research was to analyze the effect of the application of fishbones waste-based edible coating on smoked catfish kabayaki product on organoleptic quality deterioration and shelf life of the product in refrigeration temperature, and the consumer preferences. Organoleptic quality deterioration was measured by descriptive analysis for 11 days of storage in refrigeration temperature. Costumer preferences was measured by hedonic test. The result shows that the application of edible coating on the product cause negative impacts on initial organoleptic quality and organoleptic quality deterioration rate of the product, especially on aroma and texture parameters. The recommended shelf life of the product was 6 days at most based on the organoleptic quality measured (all the parameters values were above 7). Hedonic test also showed negative impacts of edible coating application on all the measured parameters. Based on the results of the research, the application of fishbones waste-based edible coating on smoked catfish kabayaki product was determined to be ineffective and was not recommended in an effort to inhibit the organoleptic quality deterioration rate of the product during refrigeration temperature storage.